Four Symposia on Flolklore - Thompson, Stith (Indiana University Press, 1953)
Originally published in 1953, Four Symposia on Folklore is a printed collection of transcribed tape recordings from the 1950 Midcentury International Folklore Conference at Indiana University. The collection is perhaps best described in the following excerpt from a 1954 review originally written by Richard M. Dorson for the Midwest Folklore journal: "Henceforth the loneliest folklorist starved for shoptalk can find congenial company at his elbow. ... This enthralling volume offers information into important work being carried on in centers of interest from Sweden to Arizona, provides rich insights ... and furnishes valuable suggestions for future lines of folkloristic endeavor. These data and ideas reach the reader ... in a medium most ideally suited to the folklorist's craft, the spontaneous spoken word, seized on tape and transported to the printed page. As an heroic attempt to pool information and focus the scattered energies of folklore enthusiasts in this country ... the Four Symposia constitutes a landmark in the history of American folklore studies."